Auditor Switching Behavior in Property, Real Estate, and Building Construction Company - Tria Nur Aysah Aysah; Aris Eddy Sarwono; Dewi Saptantinah Puji Astuti (Fakultas Ekonomi dan Bisnis Islam, UIN Sunan Kalijaga Yogyakarta, 2022)
In the face of the threat of familiarity or trust, auditors can be excessively influenced by senior executives and become overly sympathetic. A relationship of trust that is too excessive can interfere with the objectivity of testing that does not match the expectations of an independent relationship. In addition, there are also threats of intimidation that auditors usually get from the dominance of directors and management. This paper proposes a study to find out what factors can influence the occurrence of auditor turnover. The analysis was carried out using secondary data on audited financial statements from 2018-2021 from 76 companies in the property, real estate, and building constructions sectors in Indonesia listed on the Indonesia Stock Exchange totaling 181 samples that met the criteria. The number of sample companies is limited to switching auditor information and other variable information. We use logistic regression models to classify variable auditor switching, audit opinion, financial distress, KAP size, audit delay, and audit report lag. The results showed that audit opinion, financial distress, KAP size did not significantly affect the occurrence of switching auditors. Meanwhile, audit delay and audit report lag significantly affect the occurrence of switching auditors.